Chemical control of an unrecorded rot of Coccinia indica caused by Bipolaris tetramera - SHARMA, VISHNUPRIYA (Indian Phytopathology, 2006)
During survey of post-harvest diseases of fruit and vegetables in the markets of Allahabad, District of Uttar Pradesh, India a serious rot of Coccinia indica Wight & Arn., was frequently encountered. Etiological studies confirmed Bipolaris tetramera (Mc Kinney) Shoemaker to be the cause of the disease; a first report. Evaluation of ten fungicides in-vitro and in-vivo showed that Dithane M-45, Ziram-500 and Anustin were effective in management of the disease.